SISTEM INFORMASI AKUNTANSI BIAYA STANDART PADA PT. INDONESIA ASAHAN ALUMINIUM (PERSERO) - Wesly Simanjuntak (LP2MTBM MAKARIOZ, 2018)
In running an organization and implementing an internal control system, the role of the accounting information system is very important. The benefits of the accounting information system can be evaluated through its impact on increasing decision-making processes, the quality of accounting information, performance evaluation, internal control, and transactions that facilitate the company. Performance management is a business discipline that has a very fast maturity. Therefore, performance management has a key role in increasing the overall value of the organization.The formulation of the problem in this study is